Analisis Implementasi Pembelajaran Berbasis Masalah Berorientasi Sosiosaintific Issue Terhadap Peningkatan Literasi Sains - Rina Oktaviana; Ulya Ruwaida; Opik Prasetyo; Zevira Fransisca Aurora; Hery Fajeriadi; Nurul Aulia (Wahana-Bio: Jurnal Biologi dan Pembelajarannya, 2026)
Abstract. Scientific literacy plays a crucial role in enabling students to understand, evaluate, and respond to scientific issues that affect society. However, findings from the Programme for International Student Assessment (PISA) and the Trends in International Mathematics and Science Study (TIMSS) indicate that the scientific literacy level of Indonesian students remains relatively low. This study aimed to investigate the improvement of students’ scientific literacy through the implementation of Problem-Based Learning (PBL) oriented toward Socioscientific Issues (SSI) in the topic of Environmental Change. This research employed a descriptive quantitative method with a pre-experimental One-Group Pretest-Posttest design. A MANOVA test yielded a significance value of 0.000 (< 0.05), indicating that the SSI-based PBL model significantly enhanced students’ scientific literacy. These findings demonstrate that SSI-oriented PBL is effective in improving scientific literacy while fostering students’ awareness of the importance of protecting the environment from the negative impacts of environmental change.